2022
DOI: 10.1007/s00424-022-02701-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic mechanisms of acute proximal tubular injury

Abstract: Damage to the proximal tubule (PT) is the most frequent cause of acute kidney injury (AKI) in humans. Diagnostic and treatment options for AKI are currently limited, and a deeper understanding of pathogenic mechanisms at a cellular level is required to rectify this situation. Metabolism in the PT is complex and closely coupled to solute transport function. Recent studies have shown that major changes in PT metabolism occur during AKI and have highlighted some potential targets for intervention. However, transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…In the post-ischaemic kidney, tubular injuries can be either lethal as apoptosis and necrosis or sublethal as disintegrations in cytoskeleton and intercellular junctional proteins, detachment of viable cells, shedding of brush borders and formation of intratubular casts. 1,[21][22][23] The most drastic epithelial cell damages in both VIR and VIR-rRPP groups occurred in the PT and TAL, because of their high active transport, 24,25 and especially in the OM-os where is primarily supplied by venous blood of ascending vasa and with a hypoxic state even in the normal condition. 18,19,23 It has been shown that bilateral renal arterial clamping in the male spontaneously hypertensive rats (SHR) compared with the female SHR and normotensive male rats results in greater VC, especially in the OM, which is associated with the development of severer AKI and more delay in recovery of the post-ischaemic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In the post-ischaemic kidney, tubular injuries can be either lethal as apoptosis and necrosis or sublethal as disintegrations in cytoskeleton and intercellular junctional proteins, detachment of viable cells, shedding of brush borders and formation of intratubular casts. 1,[21][22][23] The most drastic epithelial cell damages in both VIR and VIR-rRPP groups occurred in the PT and TAL, because of their high active transport, 24,25 and especially in the OM-os where is primarily supplied by venous blood of ascending vasa and with a hypoxic state even in the normal condition. 18,19,23 It has been shown that bilateral renal arterial clamping in the male spontaneously hypertensive rats (SHR) compared with the female SHR and normotensive male rats results in greater VC, especially in the OM, which is associated with the development of severer AKI and more delay in recovery of the post-ischaemic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal renal tubule is a major site for tubular damage and proximal tubule injury is the most frequent cause of AKI. Therefore, it is important to identify the site of injury [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced kidney injury (DIKI) is a major concern in the clinical use of nephrotoxic drugs as well as in the drug development process 1,2 . Renal tubular epithelial cells (TECs) are particularly sensitive to druginduced toxicity because of their pivotal role in the reabsorption and metabolism of xenobiotics 3,4 . Acute tubular necrosis is the most common cause of acute kidney injury (AKI) 5 .…”
Section: Introductionmentioning
confidence: 99%